Social Change-based Identity Negotiation: Case of “Cina Benteng” and Indigenous Community in Kalipasir Tangerang, Banten - Liza Diniarizky Putri; Abdul Malik; Selly Novinka Putri; Hellya Sri Hartani (JSW (Jurnal Sosiologi Walisongo), 2022)
Chinese and indigenous people in Kalipasir have lived together for centuries. Although they experienced various social changes due to changes in spatial planning, job opportunities, and cultural recognition, they still live in harmony by negotiating its identity. This study will reveal the factors driving the negotiation of the identity of the people of Kampung Kalipasir; the ways of the identity negotiation in Kalipasir Village take place; and the impact of identity negotiation on people's attitudes to social change. Applying qualitative research, this study reveals that identity negotiations are driven by factors of cultural diversity, economic equality, and the presence of a common enemy. The form of identity negotiation that occurs is manifested in three behaviors, namely tolerance, prioritizing togetherness, and maintaining tradition. The consequences of this identity negotiation led to a multicultural attitude, prioritizing deliberation, and rejecting exclusivity. This finding shows that a multicultural society can develop in response to social change without having to become a hybrid society by negotiating a tolerant identity and building togetherness while still maintaining traditional values.